Watershed seasonality regulating vanadium concentrations and ecological risks in the coastal aquatic habitats of the northwest Pacific. (1st April 2023) - Tulcan, Roberto Xavier Supe; Ouyang, Wei; Guo, Zewei; Lin, Chunye; Gu, Xiang; Wang, Aihua; Wang, Baodong
Abstract: Vanadium is a component of different natural and industrial products and a widely used metal, which, nonetheless, has only garnered attention in recent years owing to its potential risks. Six sampling trips were conducted over different seasons and years, collecting 108 samples from rivers and 232 from the bays and analyzed using high-precision inductively coupled plasma mass spectrometry. This study investigated the sources, spatiotemporal characteristics, and risks of vanadium in the aquatic ecosystems of two typical bays of the Northwest Pacific that have strong links with vanadium-related industries. Likewise, the health and ecological risks were assessed using probabilistic and deterministic approaches. Overall, vanadium concentrations were higher in Jiaozhou Bay (JZB: 0.41–52.7 μg L −1 ) than in Laizhou Bay (LZB: 0.39–17.27 μg L −1 ), with concentrations higher than the majority of the worldwide studies. Vanadium-realted industries significantly impacted ( p  < 0.05) the metal concentrations in the rivers with 54.22% (40.73–150%) and 54.45% (27.66%–68.87%) greater concentrations in JZB and LZB rivers. In addition, vanadium exhibited significant seasonal variation, and higher values were quantified during the monsoon period at LZB owing to the greater catchment area. Impacted by smaller freshwater inputs, the post-monsoon period had substantial impacts on JZB, and vanadium in the rivers and bays was significantly higher during the winter. Despite some concentrations being higher than that indicated in the drinking water guidelines established by China, vanadium presents low to null risks to the population as per both approaches. Last, species with limited resilience are likely to face medium to high risks, with an incidence of 65–93% using the probabilistic method and 52–97% using the deterministic assessment. Graphical abstract: Image 1 Highlights: Concentrations in water near vanadium-related industries are up to 54.45% higher. Seasonal variations in the vanadium concentrations linked with vanadium adsorption capacity. Vanadium concentrations in both study areas higher than those found across China. Medium and high ecological risks were estimated for both bays.